2020
DOI: 10.1002/aelm.202000674
|View full text |Cite
|
Sign up to set email alerts
|

Low‐Voltage Operable and Strain‐Insensitive Stretchable All‐Carbon Nanotube Integrated Circuits with Local Strain Suppression Layer

Abstract: Stretchable devices, which can intimately contact dynamic free‐form surfaces, show great promise for wearable and implantable devices for human beings and multifunctional electronic skins for soft robotics. Although some successful stretchable devices have been reported, there are still remaining issues; in particular, the fundamental requirements for wearable devices, including low‐voltage operation, operation speed, mechanical stretchability and robustness, and easy circuit design, are needed to be satisfied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Recent progress in this field has brought remarkable advances, leading to a variety of curved devices with unique applications in human–computer interaction, imaging, and environmental sensing. [ 17–19 ] Currently, deterministically patterned stretchable circuits (e.g., circuits employing an island–bridge structure or a local strain suppression layer) form the basis for the most complex, cutting‐edge examples of nondevelopable electronics, including thin‐film transistors, [ 20 ] ultrasonic transducers, [ 13 ] curved imagers, [ 14,21 ] and thermoelectric energy harvesters. [ 22 ] These devices integrate small chip devices, often made of high‐performance electronic materials such as silicon or metal, with wavy or kirigami‐inspired interconnects, ensuring that any tensile strain applied to the system is concentrated in the wiring instead of the chips.…”
Section: Introductionmentioning
confidence: 99%
“…Recent progress in this field has brought remarkable advances, leading to a variety of curved devices with unique applications in human–computer interaction, imaging, and environmental sensing. [ 17–19 ] Currently, deterministically patterned stretchable circuits (e.g., circuits employing an island–bridge structure or a local strain suppression layer) form the basis for the most complex, cutting‐edge examples of nondevelopable electronics, including thin‐film transistors, [ 20 ] ultrasonic transducers, [ 13 ] curved imagers, [ 14,21 ] and thermoelectric energy harvesters. [ 22 ] These devices integrate small chip devices, often made of high‐performance electronic materials such as silicon or metal, with wavy or kirigami‐inspired interconnects, ensuring that any tensile strain applied to the system is concentrated in the wiring instead of the chips.…”
Section: Introductionmentioning
confidence: 99%
“…Reproduced with permission. [288] Copyright 2017, Wiley-Blackwell. g) Device structure schematic of stretchable CNT FET with L-SSL, and FEA of stretchable PDMS substrate with L-SSL under 50% uniaxial tensile strain.…”
Section: Stiffness Engineeringmentioning
confidence: 99%
“…A representative design for strain suppression in the transistor region of a stretchable FET array was the study reported by Nishio et al. [ 38 ] In their work, an uniaxially stretchable electronic circuit was proposed by incorporating a low strain suppression layer (L‐SSL) of Parylene C into the conventional bottom‐gate‐top‐contacted CNT transistor array. By encapsulating the OSC channel with the L‐SSL, whose Young's modulus was different with the substrate material, strains were successfully controlled in the lower modulus interspace, with marginal strain distributed in the transistor region.…”
Section: Structural Designing For Sensitivity Modulationmentioning
confidence: 99%